2004
DOI: 10.1093/dnares/11.5.325
|View full text |Cite
|
Sign up to set email alerts
|

A 210-kb Segment of Tandem Repeats and Retroelements Located between Imprinted Subdomains of Mouse Distal Chromosome 7

Abstract: Mammalian genes subject to genomic imprinting often form clusters and are regulated by long-range mechanisms. The distal imprinted domain of mouse chromosome 7 is orthologous to the Beckwith-Wiedemann syndrome domain in human chromosome 11p15.5 and contains at least 13 imprinted genes. This domain consists of two subdomains, which are respectively regulated by an imprinting center. We here report the finished-quality sequence of a 0.6-Mb region encompassing the more centromeric subdomain. The sequence contains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 0 publications
1
17
0
Order By: Relevance
“…Deletion of 260 kb of the Begain-Dlk1 LINE-1 repeat array A large intergenic repeat cluster containing tandem repeat and retroelements has previously been reported between the Igf2/H19 and Kcnq1 imprinted domains; it has been proposed that this cluster may act as a target for epigenetic modifications that regulate imprinting (Shirohzu et al 2004). To investigate whether the recently evolved, long, dense, lamina-associated LINE-1 array in the Dlk1/Dio3 domain might have an impact upon imprinting and gene regulation, it was subjected to targeted deletion by homologous recombination in embryonic stem (ES) cells using vectors from the Mutagenic Insertion and Chromosome Engineering Resource (MICER) (Adams et al 2004).…”
Section: Characterization Of Line-1 Repeat Array In the Dlk1-dio3 Impmentioning
confidence: 99%
“…Deletion of 260 kb of the Begain-Dlk1 LINE-1 repeat array A large intergenic repeat cluster containing tandem repeat and retroelements has previously been reported between the Igf2/H19 and Kcnq1 imprinted domains; it has been proposed that this cluster may act as a target for epigenetic modifications that regulate imprinting (Shirohzu et al 2004). To investigate whether the recently evolved, long, dense, lamina-associated LINE-1 array in the Dlk1/Dio3 domain might have an impact upon imprinting and gene regulation, it was subjected to targeted deletion by homologous recombination in embryonic stem (ES) cells using vectors from the Mutagenic Insertion and Chromosome Engineering Resource (MICER) (Adams et al 2004).…”
Section: Characterization Of Line-1 Repeat Array In the Dlk1-dio3 Impmentioning
confidence: 99%
“…However, notable differences also exist. In mouse, the region between Th and Ins2 is over 200 kb and contains an extraordinarily high concentration of tandem repeats, long interspersed nuclear element (LINE) retrotransposons and endogenous retroelements (Shirohzu et al, 2004). This repeat-rich region also exhibits asynchronous replication, similar to the rest of the domain, and contains 18 matrix attachment regions (Yatsuki et al, 2000;Purbowasito et al, 2004).…”
Section: Kcnq1ot1 Length and Functionmentioning
confidence: 99%
“…In human, the distance between TH and INS is considerably shorter (~10 kb). However, a highly repetitive region that is enriched for LINEs and SINEs (short interspersed elements) and retroelements is found between ASCL2 and TH (a ~115 kb region) in humans (Shirohzu et al, 2004) and in the marsupial tammar wallaby (Ager et al, 2008). If repetitive regions play a role in boundary function, this might indicate that the boundary between the KCNQ1OT1 and H19 domains in humans is within the ASCL2 and TH repetitive region.…”
Section: Kcnq1ot1 Length and Functionmentioning
confidence: 99%
“…We recently reported a 0.6-Mb mouse sequence corresponding to this sequence (Shirohzu et al 2004). Comparisons of the two sequences revealed that the gene order and transcriptional polarities are conserved except that two genes/transcripts are missing in chickens (see below).…”
Section: Isolation and Sequencing Of Chicken Bac Clonesmentioning
confidence: 99%